Exploration of the anti-inflammatory potential of Polygonum bistorta L.: protection against LPS-induced acute lung injury in rats via NF-ĸβ pathway inhibition - Parveen, Sajida; Khan, Kashif ur Rehman; Iqbal, Shahid Muhammad; Aati, Hanan Y.; Al-taweel, Areej M.; Hussain, Liaqat; Hussain, Musaddique (Frontiers in Pharmacology, 2025)
Traditional medicine uses the roots and rhizomes of Polygonum bistorta L. (Polygonaceae) to treat cough, bronchitis, and other respiratory infections. Our goal was to gain insights into the lung protective effects of the roots of P. bistorta L. against lipopolysaccharide-induced acute lung injury in rats, along with the possible mechanism(s). The outcomes revealed deliberate quantities of the total phenolic and flavonoid contents of 156.2 ± 5.13 GAE/g and 179.45 ± 2.08 mg QE/g, respectively. Crude extract possesses a maximum inhibitory potential of 81.77% ± 0.62% for acetylcholinesterase against eserine. Acute oral toxicity study revealed LD50 beyond 7 g/kg. Plant extract markedly restored LPS-induced hypoxemia, pulmonary edema, histopathological alterations, and leukocyte infiltration in the lung. ELISA testing on BALF found that the plant extract efficiently reinstated superoxide dismutase, total anti-oxidant capacity, malondialdehyde, and total oxidative stress. qRT-PCR indicated a decline in the endotoxin-induced overproduction of pro-inflammatory markers, oxidative stress, transcription factor, and downregulated antioxidant potential in extract-treated groups. Furthermore, 24 metabolites were identified and quantified via GC-MS. A molecular docking procedure was implemented on the bioactive metabolites that were identified to evaluate their potential for inhibiting AChE. In conclusion, P. bistorta roots mitigate inflammation and oxidative stress by improving redox signaling and NF-ĸβ (p65) pathways and can thus play a role in strategies for overcoming therapeutic challenges.